Uvod v hidravlično pogonsko-krmilno tehniko - Lovrec, Darko (University of Maribor Press, 2018)
Introduction to Hydraulic Drive Control Technology. Hydraulic drives and controls can be spotted in all areas of technique. In recent decades, this technique has become a key technology wherever there is a high density of energy in the foreground - a small mass and volume of components with high power. In the field of stationary devices, these are presses, machines for the processing of plastic materials, machines and devices in ironworks and rolling mills, transport and testing devices and machining machines. This technique is indispensable in the field of a wide variety of agricultural, forestry and construction machinery, and in aviation and nautics. The textbook Introduction to hydraulic drive control technology introduces basic information on the structure of hydraulic systems, the transmission of power, forces, and motions using a hydraulic fluid. It is intended for students of a higher education program in mechanical engineering. It is also intended for anyone who is still experiencing this technique, as it provides the first insight into the background of the operation of these systems. Therefore, in the presentation of individual characteristics, complex mathematical equations and derivatives are not used, but merely the basic ones necessary for the basic calculations or selection of suitable hydraulic components. All the key components of the hydraulic system are presented in a simple and transparent manner: from hydraulic fluid to all other "real" components, i.e. hydraulic pumps and motors, important types of valves, their tasks and basic structures and other components necessary for proper functioning of the entire hydraulic system.